Description of the immature stages of the endangered Japanese endemic Oreodytes kanoi (Kamiya, 1938) (Coleoptera: Dytiscidae: Hydroporinae) and comparison with the known larvae of Oreodytes Seidlitz, 1887 - Okada, Ryohei; Alarie, Yves (Zootaxa, 2020)
The larvae and pupa of the Japanese endemic Oreodytes kanoi (Kamiya, 1938) are described and compared with those known of other species of Oreodytes Seidlitz, 1887. Larvae of O. kanoi and other species of the alpinus species-group share the presence of dorsal secondary setae on tarsi, a unique feature amongst Oreodytes. The morphology of the pupa of O. kanoi is briefly discussed with some information on the ecology of this species.